THE EFFECT OF CULTURE MEDIA TYPE AND PLANT GROWTH REGULATORS ON CALLUS INDUCTION OF OIL PALM (Elaeis guineensis Jacq) PISIFERA TYPE - Sulaksono, Gogoh; Hasmeda, Mery; Hanum, Laila; Wendra, Fahmi; Santika, Baitha; Asmono, Dwi (BIOVALENTIA: Biological Research Journal, 2021)
Oil palm has a high economic value since it is one of the highest vegetable oil-producing plants compared to other oil-producing plants. The provision of good planting material for oil palm plantations is one of the determining factors to increase productivity. The parent Pisifera type of oil palm is important to develop the high-yielding oil palm Tenera varieties. The provision of oil palm material could be done through generative system with seeds and also could be done through vegetative approaches using tissue culture techniques. It aims to get plants that are genetically the same as their parents (true to type). The purpose of this study was to see the effect of different type of tissue culture media and plant growth regulators (PGR’s) on the callus induction stage of Pisifera type oil palm. The results show that the treatment using Murasige and Skoog (MS) culture media is able to give a better effect when compared to the use of Eeuwens and Blake (Y3) basic media. While the use of PGR treatment (H6 = NAA 6 mg/l + 2.4-D 0.5 mg/l) showed a callus growth percentage of 76%, which was better than (H1 = Kin 0.1 mg/l + 2.4-D 100 mg/l) by 42%.